18F-FDG PET/MR reveals specific brain metabolic features in Parkinson’s disease with frailty - Li, Guoyang; Zhang, Wenli; Mao, Fengju; Zhao, Hong; Zhao, Long; Yang, Yang; Sun, Chang; Liu, Lu; Wang, Xiangcheng; Luo, Xiaoguang (Frontiers in Aging Neuroscience, 2026)
BackgroundFrailty is significantly more prevalent in individuals with Parkinson’s disease (PD) than in general population, yet the underlying neuropathophysiological mechanisms remain poorly understood. This study aimed to characterize the clinical features and cerebral metabolic patterns of frail PD patients using [18F]-fluorodeoxyglucose positron emission tomography (18F-FDG PET), and to explore the potential pathophysiological mechanisms.MethodsA total of 64 PD patients treated at Shenzhen People’s Hospital underwent 18F-FDG PET/MR imaging during June-December 2024. Age- and sex-matched healthy controls were also recruited (n = 17). For PD patients, frailty was assessed using the Fried criteria. Patient demography, cognitive performance, and clinical variables—including UPDRS-III scores—were compared between frail and non-frail PD patients. Regional brain metabolism, measured as 18F-FDG SUVr, was analyzed in brain regions defined by the Automated Anatomical Labeling (AAL) atlas.ResultsAmong the PD cohort (mean age: 66.86 ± 6.97 years; 30 female), 34 were classified as non-frail (mean age: 64.29 ± 6.61 years; 16 female) and 30 as frail (mean age: 69.77 ± 6.17 years; 14 female). Compared to the non-frail group, frail PD patients were significantly older (P = 0.001) and exhibited more severe motor symptoms (UPDRS-III, P < 0.001; modified Hoehn & Yahr (Modified H&Y) stage, P = 0.028), along with greater cognitive impairment (P < 0.001). Although the daily levodopa equivalent dose did not differ significantly between groups (P = 0.076), a trend toward higher dosage was observed in the frail group. 18F-FDG PET/MR analysis revealed significantly reduced glucose metabolism in 13 brain regions in frail PD patients compared to non-frail patients: Frontal_Mid_L (P = 0.0056), Frontal_Mid_Orb_L (P = 0.0045), Frontal_Inf_Tri_R (P = 0.0053), Occipital_Mid_L (P = 0.0035), Occipital_Inf_L (P = 0.0053), Parietal_Inf_R (P = 0.0003), Angular_L (P = 0.0015), Angular_R (P = 0.0003), Caudate_L (P = 0.0052), Caudate_R (P = 0.0019), Temporal_Mid_R (P = 0.0040), Temporal_Inf_L (P = 0.0048), and Temporal_Inf_R (P = 0.0046). Correlation analyses revealed distinct region-function associations in the cognitive domains of frail PD patients. Regression analysis indicated that hypometabolism in the Temporal_Inf_R was significantly associated with UPDRS-III scores in the frail group.ConclusionFrailty in PD is associated with advanced age, greater motor severity, and possibly increased medication needs. Frail PD patients exhibit specific patterns of cerebral hypometabolism and more severe cognitive deficits. Distinct brain regions are differentially associated with specific cognitive domains. Notably, reduced metabolism in the Temporal_Inf_R is significantly related to motor symptom severity in frail PD, suggesting a key region in the pathophysiology of frailty in PD.